Government Expenditure and Deficit Financing: The Ghanaian Post-War Experience (Journal of Science and Technology, 2016)
In this paper, the author has tested the Buchanan – Wagner hypothesis for Ghana using post war annual data, based on traditional formulation by Nisakanen (1978) as well as the Error- Correction model as used by Cragwell (1999) for BabadosThe results for Ghana rejected the hypothesis. In other words, the Ghanaian experience indicated that high deficit do not necessarily encourage increased government spending: so that the population tended to take full cognizance of its tax liabilities as entailed in debt servicing.This conclusion contrasted variously with the results in similar studies for Babados, Pakistan and Greece: and therefore suggest that, the applicability or otherwise of the Buchanan – Wagner hypothesis for developing economies may be mixed and country – specify.The results have also shown that productivity growth in the public sector in Ghana during the survey period exceeded that of the private sector, but more important, there was the tendency for the high growth in the former to spill – over to the latter: but first, public to the sector activity had to “crowed in” or complement activities in the private sector.